60 GHz frequency divider - Thia, Boon Wah (2014)
This report contains an introduction to the basic concepts behind Injection- Locked Frequency Dividers (ILFD). In addition, literature review of LC CMOS ILFD is performed and the results were reproduced using Cadence SpectreRF simulator in 65nm CMOS technology. The author studied the reference design and analyzed how the topology that was chosen by the paper were able to enhance the locking range of the Injection-Locked Frequency Divider.The stimulation results and steps of a